REGIONAL INTEGRATION AND THE PROMOTION OF SOCIO-ECONOMIC DEVELOPMENT IN AFRICA: AN ANALYSIS THROUGH THE LENS OF THE REGIONAL ECONOMIC COMMUNITIES - (:unkn) unknown (My University, 2025)
Adopted on 3 June 1991 in Abuja by the 51 Heads of State of the member states of the former OAU, the Abuja Treaty aims to create the African Economic Community and to accelerate, from the Regional Economic Communities (RECs), the process of regional integration and consequently the promotion of Africa's socio-economic development. However, more than three decades after the adoption of the Abuja Treaty and four years before its expiry in 2028, the implementation of the process of building the AEC and promoting the socio- economic development of the continent has fallen short of the initial projections in terms of the results achieved. It is from this observation that this study, entitled Regional Integration and the Promotion of Socio-Economic Development in Africa: An Analysis through the Lens of the Regional Economic Communities, was drawn up. The study is based on the question: Do Africa's current Regional Economic Communities help to promote regional integration and socio-economic development in Africa? Our study focuses on optimising the process of regional integration in Africa with a view to the effective establishment of the African Economic Community and the promotion of socio-economic development. Referring to the theoretical fields of structuralism and comparative advantage, we have established that, since the end of the Second World War, regional integration has been perceived by states as an instrument for preserving peace and promoting socio-economic development. It is for this reason that regional integration has been favoured on all continents and has made it possible to strengthen cooperation for peace and development between countries such as those in Africa, despite a number of identified drawbacks. To this end, we have successively highlighted the political-structural and macroeconomic constraints in our study. This research leads to the following conclusions: the political-structural reorganisation and macroeconomic reframing of the
Keywords: African Research